A cross-sectional study assessing the association between online ratings and clinical quality of care measures for US hospitals: results from an observational study. - Emmert, Martin; Meszmer, Nina; Schlesinger, Mark (BMC Health Services Research, 2018)
BACKGROUND Little is known about the usefulness of online ratings when searching for a hospital. We therefore assess the association between quantitative and qualitative online ratings for US hospitals and clinical quality of care measures. METHODS First, we collected a stratified random sample of 1000 quantitative and qualitative online ratings for hospitals from the website RateMDs. We used an integrated iterative approach to develop a categorization scheme to capture both the topics and sentiment in the narrative comments. Next, we matched the online ratings with hospital-level quality measures published by the Centers for Medicare and Medicaid Services. Regarding nominally scaled measures, we checked for differences in the distribution among the online rating categories. For metrically scaled measures, we applied the Spearman rank coefficient of correlation. RESULTS Thirteen of the twenty-nine quality of care measures were significantly associated with the quantitative online ratings (Spearman p = ±0.143, p < 0.05 for all). Thereof, eight associations indicated better clinical outcomes for better online ratings. Seven of the twenty-nine clinical measures were significantly associated with the sentiment of patient narratives (p = ±0.114, p < 0.05 for all), whereof four associations indicated worse clinical outcomes in more favorable narrative comments. CONCLUSIONS There seems to be some association between quantitative online ratings and clinical performance measures. However, the relatively weak strength and inconsistency of the direction of the association as well as the lack of association with several other clinical measures may not enable the drawing of strong conclusions. Narrative comments also seem to have limited potential to reflect the clinical quality of care in its current form. Thus, online ratings are of limited usefulness in guiding patients towards high-performing hospitals from a clinical point of view. Nevertheless, patients might prefer different aspects of care when choosing a hospita